Structural design. An introduction to the art and science of designing structures. - Haynes (London : Thomas Telford Ltd., 2013)
ICE Textbooks' provide clear, accurate and relevant information on the major principles of civil and structural engineering at a level suitable for undergraduate students worldwide. Divided into easily understandable modules,'ICE Textbooks' feature worked examples, practice questions and learning point summaries throughout. This book provides an introduction to structural design for civil engineering students on undergraduate courses. Covering topics from conceptual design to communication, and material utilisation and structural element design to design philosophy,'Structural Design: An introduction' to the art and science of designing structures is a simple and clear text, presenting the core material using the author's extensive experience.